Maintaining a good ventilatory efficiency in the transition between normoxia and hypoxia at rest predicts a better oxygenation during exercise in hypoxia - Papi Renzetti, G.; Giardini, G.; Mandolesi, G.; Cogo, A. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Exposure to acute H induces a sudden increase in ventilation (VE) to maintain satisfactory oxygen saturation (SaO2). It has been shown that a ventilatory pattern characterized by low respiratory rate (RR) and high tidal volume (VT) for the same amount of VE is associated to better SaO2 (1, 2) and subjects adopting slower and deeper breathing maintain a better SaO2 at altitude due to a better ventilatory efficiency (IE). IE is the ventilation (VE) required to achieve a given level of SaO2. The relative changes in VE and %SaO2 is the index of ventilatory efficiency (IE index = SaO2/VE corrected by height). AIM To assess the influence of different breathing patterns on SaO2 during H exposure. Method: We tested the ventilatory adaptation and SaO2 in 36 mountain guides (M age 29-57) at rest in N, and at rest and during exercise in H simulating 4500m (Altitrainer, Simtec, CH; Quark, COSMED, I). For each frame we calculated the mean value of VE, VT, RR and the IE. Data during exercise refer to the same work intensity. Results: As expected, VE increased and SaO2 decreased in H vs. N, changing further during exercise. According to the difference in IE between N and H at rest (ÄSaO2/VE) we divided the subjects into 4 groups: High Efficiency (+ 1.36), Moderate (-1.16), Mild (-3) and Low (-5.4). In group High, the SpO2 during exercise is higher than in group Low (76.8 vs. 64.66 p = 0.027) with a significantly greater increase in VT as compared to RR for the same increase in VE. A significant correlation is found between the ÄSpO2/VE at rest and the oxygen desaturation during exercise in H (r=0.46 p=0.005). Conclusion: We conclude that subjects with a better IE at rest in H, spontaneously adopting slower and deeper ventilation, have the capability to maintain a better oxygenation during exercise in H.